Bounded approximate synthesis of the optimal control for the wave equation - Sukretna, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We consider the problem of optimal control for the wave equation. For the formulated problem, we find the optimal control in the form of a feedback in the case where the control reaches a restriction, construct an approximate control, and substantiate its correctness, i.e., prove that the proposed control realizes the minimum of the quality criterion.